2005
DOI: 10.1200/jco.2005.02.7045
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins and Breast Cancer: A Meta-Analysis of Seven Randomized Clinical Trials and Nine Observational Studies

Abstract: Our meta-analysis findings do not support a protective effect of statins against breast cancer. However, this conclusion is limited by the relatively short follow-up times of the studies analyzed. Further studies are required to investigate the potential decrease in breast cancer risk among long-term statin users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(156 citation statements)
references
References 55 publications
7
146
0
3
Order By: Relevance
“…Similarly, four large cohort studies found no association between statin use and risk of breast cancer [3,5,7,8], although one study observed an 18% lower breast cancer incidence with use of lipophilic statins [5]. A meta-analysis [23] conducted in late 2005 of nine observational studies, including those mentioned above, and seven clinical trials found that statin use did not significantly affect the risk of breast cancer using either a fixed-effects model (RR = 1.03; 95% CI: 0.93-1.14) or random effects model (RR = 1.02; 95% CI = 0.89-1.18). Stratification by study design did not appreciably change the effect estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, four large cohort studies found no association between statin use and risk of breast cancer [3,5,7,8], although one study observed an 18% lower breast cancer incidence with use of lipophilic statins [5]. A meta-analysis [23] conducted in late 2005 of nine observational studies, including those mentioned above, and seven clinical trials found that statin use did not significantly affect the risk of breast cancer using either a fixed-effects model (RR = 1.03; 95% CI: 0.93-1.14) or random effects model (RR = 1.02; 95% CI = 0.89-1.18). Stratification by study design did not appreciably change the effect estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, we explored the possibility that lipophilic statin users among a cohort of (7,8,(15)(16)(17), we adopted a pharmacologic classification widely used by cardiovascular researchers in which pravastatin and rosuvastatin are considered hydrophilic statins, whereas other approved statins are considered lipophilic (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly growing number of epidemiologic studies addressing statins and cancer incidence has been both provocative and mixed, prompting several recent metaanalyses, which have generally concluded that there is no convincing clinical evidence supporting either a cancerpromoting or cancer-preventing effect for statins (7,8). However, subsequent commentaries have detailed many perceived deficiencies in these meta-analyses and the studies they analyzed (9)(10)(11)(12)(13)(14), including the confounding effect of combining lipophilic (e.g., lovastatin and simvastatin) and hydrophilic (e.g., pravastatin) statin users, lack of assessment of duration of statin use, and failure to consider clinically important cancer subtypes, such as breast cancers typed according to estrogen receptor (ER) and progesterone receptor (PR) status (ER/PR positive, ER/PR negative).…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory studies, statins have been shown to halt the growth, survival and migration of certain cancer cells. Though it is believed that statins on their own were associated with a reduction in breast cancer, recent study reviewed here found that statins had no effect at all on the risk of several cancers, including breast cancer (9,10). The target enzyme for cholesterollowering statins, HMG-CoA Reductase is associated with improved prognosis among ERpositive breast cancer patients, whereas ER negative patients seem to have a better outcome when HMG-CoAR is absent (11).…”
Section: Aetiological Factors Of Breast Cancer Effects Of Certain Drumentioning
confidence: 99%